1993
DOI: 10.1096/fasebj.7.13.8405815
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthesis inhibition induces leukocyte adhesion via superoxide and mast cells

Abstract: Recent work has demonstrated that inhibition of nitric oxide production with various nitric oxide synthesis inhibitors (L-NAME, L-NMMA) initiate leukocyte adhesion to postcapillary venules. The objective of this study was to elucidate the mechanism (or mechanisms) that promote the L-NAME-induced leukocyte response. Intravital microscopy was used to examine 25-40 microns venules in the rat mesentery. Nitric oxide synthesis was inhibited with L-NAME and leukocyte adhesion was observed over the first 60 min. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1
9

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 317 publications
(149 citation statements)
references
References 0 publications
5
134
1
9
Order By: Relevance
“…The isoform responsible for NO production during inflammation is the calcium-independent iNOS. 29 iNOS has been shown to be strongly upregulated in a wide variety of tissues, including the brain, after the administration of LPS. 30 Further, increased iNOS activity was found in circulating neutrophils of septic shock patients compared with healthy volunteers.…”
Section: Lps Upregulates Inos In a Complement-dependentmentioning
confidence: 99%
“…The isoform responsible for NO production during inflammation is the calcium-independent iNOS. 29 iNOS has been shown to be strongly upregulated in a wide variety of tissues, including the brain, after the administration of LPS. 30 Further, increased iNOS activity was found in circulating neutrophils of septic shock patients compared with healthy volunteers.…”
Section: Lps Upregulates Inos In a Complement-dependentmentioning
confidence: 99%
“…A single study has reported mast cell derived ANXA1 as mediating the stabilising effect of interleukin-2, determined as inhibition of histamine release (Tasaka et al 1994). Due to the pivotal location of the mast cell and its role not only in initiation but possibly also in resolution of inflammation (Kubes et al 1993, Gotis-Graham et al 1998, Woolley 2003, it is likely that a role for ANXA1 in this cell type will soon emerge.…”
Section: Anxa 1 Actions On Other Cellsmentioning
confidence: 99%
“…A inibição do NO leva aumento no nível de antioxidantes e ativação de mastócitos que se degranulam e aumentam a permeabilidade vascular. A degranulação de mastócitos pode ser inibida pela adição de doadores de NO 44,45 . Porém, segundo SALVEMINI e col. (1996) 46 , o NO é um potente vasodilatador e seu envolvimento na resposta inflamatória pode ter relação com sua habilidade em aumentar a permeabilidade vascular e o edema através de mudanças no fluxo sangüíneo local e do aumento na produção de prostaglandinas pró-inflamatórias.…”
Section: óXido Nítrico E Permeabilidade Vascularunclassified